The People VS. Paternalism: Building a consumer-led movement against lifestyle regulation - Christopher Snowdon (Institute of Economic Affairs (IEA), 2025)
Mancur Olson explained in The Logic of Collective Action (1965) that the free rider problem and the paradox of participation discourage rational consumers from taking collective action to oppose policies that disadvantage them. The lack of grassroots opposition to 'nanny state' policies from vapers, gamblers, drinkers, etc. seems to bear out this analysis. Proponents of government paternalism have overcome the problems Olson identified by securing funding from state agencies or by offering selective incentives to their supporters. Since consumers are unlikely to mobilise to fight for collective benefits, a grassroots movement opposing lifestyle regulation must rely on selective benefits, but this avenue has not been adequately explored by policy entrepreneurs. This paper outlines what such a grassroots organisation would look like and how it could be established.
Keywords: 330